2018
DOI: 10.1002/jbio.201800189
|View full text |Cite
|
Sign up to set email alerts
|

Nebulization as a tool for photosensitizer delivery to the respiratory tract

Abstract: To this day, any photosensitizers for the photodynamic treatment of pulmonary illnesses have been administered intravenously. There is, however, an intrinsic difficulty in reaching the target cells or bacteria in the respiratory system. Nebulization could overcome distribution problems and alleviate side effects by delivering the photosensitizers directly to the lungs. In this study, we evaluated the viability of three photosensitizers (indocyanine green, the chlorine Photodithazine®, and the porphyrin Photoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 36 publications
0
31
0
1
Order By: Relevance
“…ICG dye is used as an indicator substance in preclinical and clinical applications [25,26]. Also, that it is possible to monitor the delivery and consumption of ICG after ICG nebulization in mice has been previously suggested [27,28]. JN-PARIb and VMN-SM1 were selected among four nebulizers.…”
Section: Resultsmentioning
confidence: 99%
“…ICG dye is used as an indicator substance in preclinical and clinical applications [25,26]. Also, that it is possible to monitor the delivery and consumption of ICG after ICG nebulization in mice has been previously suggested [27,28]. JN-PARIb and VMN-SM1 were selected among four nebulizers.…”
Section: Resultsmentioning
confidence: 99%
“…This is similar to what has been previously described for ICG and 780 nm using other quantification methods. [10,27] The rate of accumulation, driven by redistribution if the ICG that initially went to the upper respiratory tract, does not exceed the rate of bleaching initially. In terms of a basic rate equation, we could assume that:…”
Section: Discussionmentioning
confidence: 99%
“…[9] An additional study proposed nebulization as a new pulmonary delivery method for photosensitizers, demonstrated its compatibility with ICG, and validated the delivery in a murine model. [10] The combination of ICG and infrared light has also been proposed for the treatment of other pulmonary pathogens. In 2013, Topaloglu et al established successful protocols for in vitro inactivation of S. aureus and Pseudomonas aeruginosa.…”
Section: Introductionmentioning
confidence: 99%
“…al proposing nebulization as a tool to deliver the PS to the respiratory tract. 42 Their conclusions suggest jet nebulization as an adequate method for delivering PSs with the optimal size and keeping stable the compounds through process to the lungs. Specifically, it was shown conditions in which ICG is deposited in the respiratory tract and activated with extracorporeal light and not cause acute lung or liver damage.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it was shown conditions in which ICG is deposited in the respiratory tract and activated with extracorporeal light and not cause acute lung or liver damage. 42 Moreover, all these studies show that ICG has a great potential to be a good PS due to its strong absorption band in the region of deeper penetration in biological tissue. Also, since it does not have a high TQY and therefore it is not likely to go through the reaction of type II, it is believed that ICG produces highly reactive free radicals, involved in the type I reaction.…”
Section: Introductionmentioning
confidence: 99%